Personal Guarantee dan Corporate Guarantee dalalam Putusan Peradilan Niaga - Siti Anisah (Jurnal Hukum IUS QUIA IUSTUM, 2002)
The appeal of statement for bankcrupt towards a trade court for the guarantors have been proposed bymany creditors when the debitor do not pay their debt on be due of debt payment and it- can be claimed. The decision of proposal for bahkcrupt of the guarantor can be fulfilled bythe.judge as long as the prerequirement of appeal for statement on bankcrupt are fulfilled, namely that the debitor have more than one creditor and one oftheir debts is due and it could be claimed, as well as guarantor have escaped his privileges.